Unveiling the Role of Smart Pinwheel Media in Supporting Alphabet Recognition Among 4-5-Year Olds - Suhada MR, Safna; Hanum, Rafidhah (Universitas Islam negeri Mahmud Yunus Batusangkar, 2025)
This study aims to analyze the use of smart pinwheel media in helping children aged 4–5 years recognize alphabet letters. The research was conducted at RA Al-Ikhsan, Banda Aceh, with samples selected using purposive sampling techniques. The research method employed was qualitative, with interviews conducted with teachers as the primary data source. Data were analyzed descriptively in a narrative form. The findings show that smart pinwheel media is effective in increasing children's interest and enthusiasm in learning alphabet letters. Additionally, the media supports children's development in letter recognition, particularly in pronunciation and the ability to associate letters with words that begin with those letters. However, several challenges were identified, including a lack of interest among some children and technical difficulties in using the media. Therefore, support from schools and training for teachers are crucial to optimizing the use of this media.